2001
DOI: 10.1103/physrevlett.86.2146
|View full text |Cite
|
Sign up to set email alerts
|

Strongly Enhanced Orbital Moments and Anisotropies of Adatoms on the Ag(001) Surface

Abstract: We present ab initio calculations for orbital moments and anisotropy energies of 3d and 5d adatoms on the Ag(001) surface, based on density functional theory, including Brooks' orbital polarization (OP) term, and applying a fully relativistic Korringa-Kohn-Rostoker -Green's function method. In general, we find unusually large orbital moments and anisotropy energies, e.g., in the 3d series, 2.57m B and 174 meV for Co, and, in the 5d series, 1.78m B and 142 meV for Os. These magnetic properties are determined ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
63
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(70 citation statements)
references
References 21 publications
7
63
0
Order By: Relevance
“…In the past, calculations 24 on the magnetocrystalline anisotropy energy ͑MAE͒ of transition-metal adatoms on Ag and Au surfaces ͑where the spin-orbit coupling is strong͒ have shown that Cr and Mn adatoms have a MAE of less than 5 meV. On Ni, the effect should be weaker, as on Cu, where the MAE of a single Co adatom was calculated 25 to be less than 1 meV.…”
Section: Limitations Of Present Calculationsmentioning
confidence: 99%
“…In the past, calculations 24 on the magnetocrystalline anisotropy energy ͑MAE͒ of transition-metal adatoms on Ag and Au surfaces ͑where the spin-orbit coupling is strong͒ have shown that Cr and Mn adatoms have a MAE of less than 5 meV. On Ni, the effect should be weaker, as on Cu, where the MAE of a single Co adatom was calculated 25 to be less than 1 meV.…”
Section: Limitations Of Present Calculationsmentioning
confidence: 99%
“…In a solid, electron delocalization and crystal field effects compete with these interactions, causing a substantial decrease of m S and partial or total quenching of m L . Theoretical calculations [7] predict such effects to be strongly reduced in TM impurities at non-magnetic surfaces owing to the decreased coordination, with implications also for the appearance of significant magnetic anisotropy (Fig. 1).…”
Section: Orbital Magnetic Moment and Magnetic Anisotropy Of Single Comentioning
confidence: 99%
“…Small clusters deposited on metal surfaces are predicted to have spin (m S ) and orbital (m L ) magnetic moments in between those of bulk compounds and free atoms [5][6][7], and to exhibit strong magnetic anisotropy with characteristic energies (E a ) of the order of 1-10 meV/atom, i.e., a factor 10 3 larger than bulk ferromagnetic metals [7,8]. In the case of single-domain particles, E a determines the orientation and stability of the magnetization and is thus a crucial parameter for most applications of magnetic materials in modern technology.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in recent years have considered the enhanced orbital moment predicted [12,13] and observed [14,15] in sub 12 nm diameter single domain particles. The enhancement of the orbital moment is highly size dependent and clearly marks the territory between magnetic atoms obeying Hund's rules, and bulk-like ferromagnetism with highly quenched orbital magnetism.…”
Section: Introductionmentioning
confidence: 99%